Investigating the correlation between serum albumin level and the prognosis of Bell's palsy. Issue 29 (23rd July 2021) - Shang, Wenfang; Hu, Haiyu; Shen, Mengxia; Wu, Jiangxia; Yu, Zelin; Xuan, Lihua
Abstract : Abstract: To investigate the correlation between the serum albumin level and the prognosis of patients with Bell's palsy. We retrospectively analyzed the clinical records of 311 inpatients with Bell's palsy (BP) in our hospital between September 2018 and October 2019. The patients were divided into 2 groups: the recovered group (with the House-Brackmann grade ⩽ 2) and the unrecovered group (with the House-Brackmann grade > 2), according to the follow-up results within 3 months after discharge. Blood test indicators (white blood cell count, neutrophil-to-lymphocyte ratio, red cell distribution width, serum albumin level, globulin level) and basic clinical data (age, sex, course of the disease, inpatient days, comorbidity of hypertension, diabetes, and hepatitis B) of the 2 groups were compared to explore whether they were correlated with the prognosis of patients with Bell's palsy. The serum albumin level of patients with BP in the unrecovered group was significantly lower than that of the recovered group (medians [interquartile range], 40.75 [38.40, 43.85] vs 44 [42.10, 46.20], P  < .001). Multivariate binary logistic regression revealed that serum albumin (odds ratio 0.772, 95% confidence interval 0.711–0.839, P  < .001) was a protective factor for BP prognosis. Serum albumin is a protective factor for the prognosis of BP. Although more prospective clinical controlled trials are needed, our study provides valuable and crucial prognostic information for physicians.